In Search of a More Inclusive and Relevant School Science Curriculum - Treagust, David (SPRINGER, 2022)
Peter Fensham had a deep concern that the school science curriculum should have a focus beyond that for academically oriented students and have a direct relevance to everyday lives. In a keynote address at ESERA 1999, later published in 2001, he offered a challenge for researchers to consider science content as being problematic and offered examples in five areas of science education where this research might progress to be more inclusive and relevant — alternative concepts about everyday events; changing curriculum emphases; the roles of affect and content; beyond processes towards fostering understanding; and concerns about science teachers’ content knowledge. In this paper, I have attempted to build on the main points in Peter’s keynote address and have identified developments since 1999 in these five areas that illustrate science educational research connected to students’ everyday lives.